The temporal trend of disease burden attributable to metabolic risk factors in China, 1990–2019: An analysis of the Global Burden of Disease study - Jin, Yingzhao; So, Ho; Cerin, Ester; Barnett, Anthony; Mubarik, Sumaira; Hezam, Kamal; Feng, Xiaoqi; Wang, Ziyue; Huang, Junjie; Zhong, Chenwen; Hayat, Khezar; Wang, Fang; et al. (Frontiers in Nutrition, 2023)
Background and aims Disease burden attributable to metabolic risk factors is rapidly increasing in China, especially in older people. The objective of the study was to i) estimate the pattern and trend of six metabolic risk factors and attributable causes in China from 1990 to 2019, ii) ascertain its association with societal development, iii) compare the disease burden among Group of 20. Methods The main outcome measures were disability-adjusted life-years (DALYs) and mortality (deaths) attributable to high fasting plasma glucose (HFPG), high systolic blood pressure (HSBP), high low-density lipoprotein (HLDL) cholesterol, high body-mass index (HBMI), kidney dysfunction (KDF), and low bone mineral density (LBMD). Average annual percent change (AAPC) between 1990 and 2019 was analyzed using Joinpoint regression. Results For all six metabolic risk factors, the rate of DALYs and death increased with age, accelerating for individuals older than 60 and 70 for DALYs and death, respectively. The AAPC value in rate of DALYs and death were higher in male than female across 20 age groups. A double-peak pattern was observed for AAPC in rate of DALYs and death, peaking at age 20 to 49 and at age 70 to 95 plus. The age-standardized rate of DALYs increased for HBMI and LBMD, decreased for HFPG, HSBP, KDF, and remained stable for HLDL during 1990 to 2019. In terms of age-standardized rate of DALYs, there was an increasing trend of neoplasms and neurological disorders attributable to HFPG; diabetes and kidney diseases, neurological disorders, sense organ diseases, musculoskeletal disorders, neoplasms, cardiovascular diseases, digestive diseases to HBMI; unintentional injuries to LBMD; and musculoskeletal disorders to KDF. Among 19 countries of Group 20, in 2019, the age-standardized rate of DALYs and death ranked 4th to 6th for HFPG, HSBP, HLDL, but ranked 10th to 15th for LBMD, KDF, HBMI, despite the number of DALYs and death ranked first to second for six metabolic risk factors. Conclusions Population ageing continuously accelerates the metabolic risk factor driven disease burden in China. Comprehensive and tight control of metabolic risk factors before 20 and 70 may help to mitigate the increasing disease burden and achieve healthy ageing, respectively.